METODE SCOR DAN AHP SEBAGAI PENGUKURAN KINERJA SUPPLY CHAIN MANAGEMENT PADA PABRIK GULA GEMPOLKREP (PERSERO) - Eka Ayu Yusliana; Muslimin Abdulrahim (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2023)
This study aims to measure or evaluate the Supply Chain Management of PG. Gempolkrep which is located in Dsn. Gempolkrep, Kec. Gedeg, Mojokerto Regency, East Java. PG. Gempolkrep is one of the agro-industrial companies of the Sugar Factory unit of PT Sinergi Gula Nusantara. This research focuses on six business processes contained in SCM, namely Plan, Source, Make, Deliver, Return, and Enable. The completion of this research uses the Supply Chain Operation Reference (SCOR) method and Analytical Hierarchy Process (AHP). Using SCOR performance attributes Reliability, Responsiveness, Agility, Cost, and Asset Management. Data collection is done by direct observation, interviews, and questionnaires. Furthermore, calculations are carried out on the metrics obtained from the approach using the SCOR method. Each metric score will be weighted priorities calculated using the AHP method. The results of this study indicate the performance of PG supply chain management. Gempolkrep "Good" as evidenced by the final result of 84.26 on a scale of 0 - 100. The final results of the Plan 0.13, Source 0.14, Make 0.15, Deliver 0.19, Return 0.19, and Enable 0.21 processes. Proposals for the factory to carry out evaluations and improvements focused on the procurement of process auxiliary materials, delivery of process auxiliary materials, and maintenance.